Pleomorfhic Adenoma in palate - Carretero Ancelmo, Daniel A (2012)
Pleomorfhic adenoma is the most common salivary gland neoplasm in both the major and minor salivary glands. It presents like a solid tumor of slow growth and asymptomatic. On minor salivary glands, the site more often affected is the hard palate, followed by the upper lip and buccal mucosa. The diagnosis is base on the histopathology features and the treatment consists at surgical excision. Here, we report a clinical case of a female 58 years old patient with a pleomorfhic adenoma, of 3 cm in dimension in the upper palate, that was treated by surgical treatment.